WOM dan Inovasi Produk sebagai Prediktor Minat Beli Konsumen Pendekatan Kuantitatif Berbasis SPSS Pada UMKM Usaha Bunda Sido Lego - Delvita Juniarsih; Fatimah.As; Ihsandra (Indo Publishing, 2025)
UMKM Usaha Bunda is a business engaged in the snack food industry. UMKM Usaha Bunda was established on October 13, 2021. UMKM Usaha Bunda is located in Sido Lego Village, Tabir Lintas District, Merangin Regency. The purpose of this study was to determine the effect of word of mouth and product innovation on consumer purchasing interest at UMKM Usaha Bunda in Sido Lego Village. The population is consumers who have purchased UMKM Usaha Bunda products, with a sample of 100 people taken based on the formula Hair et al = number of indicators x 5-10, with the description of each indicator X 2. The analysis used is multiple linear regression with the help of the SPSS (Statistical package social science) application program Version 23. The results of this study indicate that word of mouth and product innovation have a simultaneous effect on consumer purchasing interest in UMKM Usaha Bunda, and partially word of mouth shows that word of mouth has a significant influence on consumer purchasing interest in UMKM Usaha Bunda, while product innovation shows that it has no influence and on consumer purchasing interest in UMKM Usaha Bunda.